Motivators for a career in sales: higher education students’ views - Handley, Brian; Shanka, Tekle (University of Liverpool, 2011)
The purpose of the present research is to contribute to the marketing literature through an exploratory review of motivators for a career in sales. Following Castleberry’s (1990) qualitative study on “The Importance of various motivational factors to college students interested in sales positions” this study empirically examined the views of University students from Australia, China (including Hong Kong), and Malaysia, measured by 26 scale items using 7-point Likert Scale. Factor analysis of these items resulted in five components comprising of 22 items that students consider to be motivational factors namely ‘working environment’, ‘leadership’, ‘recognition’, ‘ancillary’ and ‘challenging’. Statistically significant differences between student groups on all components are reported.